Meningkatkan Kompetensi Menyusun Rencana Pelaksanaan Pembelajaran (RPP) melalui Bimbingan Berkelanjutan pada Guru SD Negeri 4 Kedondong Pesawaran Lampung, Tahun Pelajaran 2022/2023 - Mulyani, Emi (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
The problem in research, namely the low competence of teachers in compiling lesson plans in accordance with the provisions of the standard process. Meanwhile, one of the teacher's tasks is to plan learning well in order to achieve the learning objectives optimally. The aim of the research is to increase competence in preparing lesson plans (RPP) through ongoing guidance to teachers at SDN 4 Kedondong Pesawaran Lampung in 2022. The results of the study show that competence in preparing lesson plans (RPP) can be improved through ongoing guidance to teachers at SDN 4 Kedondong Pesawaran Lampung in 2022/2023 Academic Year.